2023
DOI: 10.1101/2023.10.30.564197
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gamma sensory stimulation and effects on the brain

Martin Kahn,
Diane Chan,
Danying Wang
et al.

Abstract: Findings by the Tsai lab and others1–8demonstrate that 40 Hz frequency sensory stimulation induces electrophysiological responses and attenuates pathology in mouse models of Alzheimer’s disease (AD). A recent study inNature Neurosciene9concluded that the stimulation does not affect endogenous gamma oscillations or amyloid burden. We welcome research investigating 40 Hz sensory stimulation, and the article by Soula et al enhances our understanding of the brain’s electrophysiological response to 40Hz. However, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In mice, visual stimulation evokes a strong intracranial 40 Hz LFP response in the visual cortex [7,9,59] and, according to one study, also in other cortical areas [9]. Interestingly, recent studies suggest that 40 Hz sensory stimulation may not engage the same circuitry that generates endogenous gamma oscillations but rather induce externally driven gamma activity [59,62,63]. In the hippocampus, three studies reported a significant increase in LFP 40 Hz power response [7,9,64], whereas one study did not [59].…”
Section: The Brain-wide Neuronal Response To Gamma Stimulationmentioning
confidence: 93%
“…In mice, visual stimulation evokes a strong intracranial 40 Hz LFP response in the visual cortex [7,9,59] and, according to one study, also in other cortical areas [9]. Interestingly, recent studies suggest that 40 Hz sensory stimulation may not engage the same circuitry that generates endogenous gamma oscillations but rather induce externally driven gamma activity [59,62,63]. In the hippocampus, three studies reported a significant increase in LFP 40 Hz power response [7,9,64], whereas one study did not [59].…”
Section: The Brain-wide Neuronal Response To Gamma Stimulationmentioning
confidence: 93%